Aortic graft infection: a hybrid and staged solution - Soares,Tony R. (2019)
Introduction: Aortic graft infection (AGI) is a life-threatening condition and a therapeutic challenge for vascular surgeons. We report a case of a complex AGI managed by a hybrid and staged strategy. Methods: Data related to the present case report were collected from hospital medical records. Results: A 51-year-old male patient, submitted 5 years ago to prosthetic aorto-bifemoral and superior mesenteric artery (SMA) bypass to treat aorto-iliac and visceral occlusive disease and a recent history of a right femoral anastomotic pseudoaneurysm managed by open surgery, was admitted to our emergency room with a left femoral anastomotic pseudoaneurysm and inflammatory signs on the right groin. The diagnostic workup (angio-CT and PET-Scan) strongly suggested infection of the aorto-bifemoral graft. A three-stage hybrid approach was then planned. In the first step, a left axillofemoral PTFE bypass was performed avoiding the infected area with ligation of the infected limb graft of the aorto-bifemoral bypass. Two weeks later, the patient was submitted to a successful endovascular recanalization of the SMA with implantation of a self-expandable bare metal stent, followed by a right axillofemoral PTFE bypass and ligation of the infected limb graft. One week later, the final stage included the exclusion of the proximal anastomosis of the visceral bypass with a covered stent in the SMA and a laparotomy for complete excision of the intrabdominal infected grafts with subsequent aortic ligation. The patient was discharged on the next three weeks on oral antimicrobial therapy. The post-op CT scan confirmed the patency of the SMA recanalization, both renal arteries, as well as the extra-anatomic bypasses to the lower limbs, with apparent resolution of the abdominal infection. Conclusion: The reported case is very unusual and represents a challenge due to the presence of a SMA bypass associated to the AGI. Endovascular recanalization of the SMA occlusion made possible the total excision of the infected abdominal grafts.